Optimalisasi Kinerja Pembelajaran Guru SMKN dengan Pendekatan Partisipatif melalui Integrasi ChatGPT dari OpenAI: Optimizing SMKN Teacher Learning Performance with a Participatory Approach through ChatGPT Integration from OpenAI - Widyaningsih, Maura; Pratama, Bayu; Herkules, Herkules; Hendartie, Susi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The mastery of constantly evolving technology is a difficult challenge for teachers at SMK Negeri 2 Palangka Raya. To overcome this, self-development through training is necessary, such as using ChatGPT to make learning more effective. ChatGPT helps find educational resources with clear commands and supports the preparation of study plans, performance objectives, and task completion. This training was held at the Digital Marketing Laboratory of SMK Negeri 2 Palangka Raya and included preparation, implementation, and evaluation. Initial evaluation showed that 65% of participants did not know about ChatGPT, 15% were somewhat knowledgeable, and 20% were knowledgeable. After the training, understanding significantly increased, with the average correct answers rising from 52% to 85%. Recommendations for sustainability include focusing on difficult material, evaluating and revising training materials, and using interactive teaching methods. Implementation of interactive teaching through approaches such as group discussions, simulations, and case studies as well as direct practice.